THE INFLUENCE OF E-CRM AND CORPORATE REPUTATION ON CUSTOMER LOYALTY WITH CUSTOMER SATISFACTION AS A MEDIATING VARIABLE (A STUDY OF PT UNIVAN GLOBAL LOGISTIK CUSTOMERS) - Ratri Wulandari; Sri Wartini (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to analyze the effect of Electronic Customer Relationship Management (E-CRM) and corporate reputation on customer loyalty, with customer satisfaction as a mediating variable at PT Univan Global Logistik. Retaining corporate customer loyalty is a crucial challenge in the competitive logistics industry. A quantitative method was employed by collecting primary data from 190 customer respondents selected through purposive sampling. Data analysis was conducted using a Structural Equation Modeling (SEM) approach based on Partial Least Squares (PLS) with SmartPLS 4.0 software. The results indicate that E-CRM and corporate reputation have a positive and significant direct effect on both customer satisfaction and loyalty. Customer satisfaction is also proven to have a positive and significant effect on customer loyalty. In the mediation testing, customer satisfaction significantly bridges the effect of corporate reputation on loyalty. However, customer satisfaction does not mediate the relationship between E-CRM and customer loyalty. In conclusion, strengthening reputation and managing digital customer relations directly impact corporate client retention, although satisfaction with E-CRM facilities does not guarantee long-term commitment without the support of operational efficiency on the ground.